Framgångsfaktorer vid ombyggnadsprojekt - Hörberg,Douglas (TVBP, 2015)
Purpose: The purpose of this study is to analyze if there are any critical success factors in renovation projects from the 1950’s in Sweden, and if they can be applied to more general construction projects. Furthermore, the study will examine how these projects are evaluated and if a wider evaluation process is needed. Finally, the study will examine how the workplace affects the residents during the project. Method: In this study a qualitative work method was used based on answers from in-depth interviews. Knowledge and data have been gathered from literature studies, interviews and a survey. These findings have then been applied to two different case studies. Conclusion: To evaluate a project from two factors, time and cost, is not enough to say whether a project is considered to be successful or not. There are several more factors to be weighed in for a complete evaluation and each person’s definition of a successful project must be considered. Instead of just an evaluation after project completion it is preferable to also implement evaluations during the project. Communication has been noted as a critical factor for success, both internal and external. Other critical factors are stakeholder satisfaction and long term business relations. The project manager has a key part in the outcome of the project and to satisfy the stakeholders objectives. Key features of a project manger is responsibility, communication, social ability and being modest. Finally, the study has shown that residents are greatly affected and they perceive the projects as stressful. Therefore, they value the communication regarding expectations and work progress.
Keywords: Framgångsfaktorer; Kritiska framgångsfaktorer; Projektledning; Underhåll; Stambyte; Ombyggnad; Flerbostadshus